Triple Negative Breast Cancer in Pregnancy and Postpartum: Two Case Reports in Hispanic Women - Ruchi Upadhyay; Qurat-Ul-Ain Butt; Abraham Hamaoui; Cassandra Henderson; Sydney McCalla; Hamid Gilak (Case Reports in Obstetrics and Gynecology)
Objective. Despite studies suggesting that triple negative breast cancer is more often seen in women of African ancestry, we report here two cases of pregnancy associated triple negative breast cancer in Hispanic women. Cases. Case one is a 37-year-old female para 2-0-0-2, who presented with a left breast mass, at 19 weeks of gestation, the biopsy of which reported an invasive ductal carcinoma, found to be triple receptor negative. The patient underwent chemotherapy during the pregnancy and was delivered with a cesarean at 37 weeks for obstetric indication. After delivery, the patient completed her chemotherapy that was followed by radical mastectomy and radiotherapy. Case two is a 28-year-old female para 6-0-1-5, who presented while breast-feeding with signs and symptoms of mastitis, and an engorged and tender right breast, five months postpartum. However, the sonogram revealed a fluid filled cavity. Aspiration and cytology did not reflect an infection and were negative for malignancy. High suspicion and lack of improvement led to biopsy that identified an invasive ductal carcinoma, found to be triple negative. The patient underwent chemotherapy followed by modified radical mastectomy. Conclusions. Triple negative breast cancer, during pregnancy or postpartum, poses a unique challenge and requires a multidisciplinary team to optimize treatment for these women.